Cytokine-dependent regulation of dendritic cell differentiation in the splenic microenvironment - Globisch, Theresa; Steiner, Nancy; Fuelle, Lorenz; Lukacs-Kornek, Veronika; Degrandi, Daniel; Dresing, Philipp; Alferink, Judith; Lang, Roland; Pfeffer, Klaus; Beyer, Marc; Weighardt, Heike; Kurts, Christian; et al. (European Journal of Immunology, 2014)
The DC-derived chemokine CCL17, a ligand of CCR4, has been shown to promote various inflammatory diseases such as atopic dermatitis, atherosclerosis, and inflammatory bowel disease. Under steady-state conditions, and even after systemic stimulation with LPS, CCL17 is not expressed in resident splenic DCs as opposed to CD8?(-) CD11b(+) LN DCs, which produce large amounts of CCL17 in particular after maturation. Upon systemic NKT cell activation through ?-galactosylceramide stimulation however, CCL17 can be upregulated in both CD8?(-) and CD8?(+) splenic DC subsets and enhances cross-presentation of exogenous antigens. Based on genome-wide expression profiling, we now show that splenic CD11b(+) DCs are susceptible to IFN-?-mediated suppression of CCL17, whereas LN CD11b(+) CCL17(+) DCs downregulate the IFN-?R and are much less responsive to IFN-?. Under inflammatory conditions, particularly in the absence of IFN-? signaling in IFN-?RKO mice, CCL17 expression is strongly induced in a major proportion of splenic DCs by the action of GM-CSF in concert with IL-4. Our findings demonstrate that the local cytokine milieu and differential cytokine responsiveness of DC subsets regulate lymphoid organ specific immune responses at the level of chemokine expression.
EVALuna2:7641